2009
DOI: 10.1093/bioinformatics/btp529
|View full text |Cite
|
Sign up to set email alerts
|

Identifying related journals through log analysis

Abstract: Motivation: With the explosion of biomedical literature and the evolution of online and open access, scientists are reading more articles from a wider variety of journals. Thus, the list of core journals relevant to their research may be less obvious and may often change over time. To help researchers quickly identify appropriate journals to read and publish in, we developed a web application for finding related journals based on the analysis of PubMed log data.Availability: http://www.ncbi.nlm.nih.gov/IRET/Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
0
11
1
Order By: Relevance
“…We can utilize them to validate the results of the content-similarity-based approach, as journals are manually We then analyze the results of the content-similarity-based approach with respect to the results of usage-based approach. We re-run the algorithm of the usage-based approach developed earlier (Lu, Xie, & Wilbur, 2009). Table 2 shows the average scores of CC, KTCC, F1 and NDCG with two different truncated positions 5 (NDCG@5) and 20 (NDCG@20) for journals with different number of published papers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We can utilize them to validate the results of the content-similarity-based approach, as journals are manually We then analyze the results of the content-similarity-based approach with respect to the results of usage-based approach. We re-run the algorithm of the usage-based approach developed earlier (Lu, Xie, & Wilbur, 2009). Table 2 shows the average scores of CC, KTCC, F1 and NDCG with two different truncated positions 5 (NDCG@5) and 20 (NDCG@20) for journals with different number of published papers.…”
Section: Resultsmentioning
confidence: 99%
“…Journal of Data and Information Science retrievals in the form of MEDLINE records that were examined by the user during that session (Lu, Xie, & Wilbur, 2009). Let A represent a journal and t A (s i ) denote the number of clicks through events that represent articles from journal A:…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Profiling journals, and measuring how different journals relate to each other, are only two of the aspects that have been examined. For example, journals can be characterized and related according to their citation patterns [1] [2] , topical similarity [3] , keyword similarity [4] , user behavior during PubMed weblog sessions [5] and even the degree of interlocking editorships [6] . Cordier [7] proposed relating journals according to the number of authors that they share, though this idea has not yet been implemented nor tested.…”
Section: Introductionmentioning
confidence: 99%
“…Both of the studies [34,35] reported semantic categorization of PubMed queries, proportion of users against number of queries, proportion of queries against number of terms in a query, and many other interesting statistical metrics. This month-long dataset has also been analyzed for: (1) identifying the journals that are related to user search queries [39] and (2) creating a database of queries that is used for automatically producing query suggestions in response to the original user’s input [40]. Both of the datasets used in Herskovic et al (2007) [29] and Doğan et al (2009) [34] are publicly available from the NLM.…”
Section: Introductionmentioning
confidence: 99%